2021
DOI: 10.3390/chemistry3030070
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemicals from Rhizophora mucronata Propagules, Its In Vitro Anti-Cancer and In Silico Drug-Likeness Potential

Abstract: This is the first report to identify the presence of 3-O-caffeoyl quinic acid (1), 4-O-caffeoyl quinic acid (2), 5-O-caffeoyl quinic acid (3), epi-catechin (4), and procyanidin B2 (5) in the young propagules of Rhizophora mucronata. Compounds 2–5 were purified and then treated against breast, colorectal, and ovarian cancer cell lines for 72 h and the results of the Sulphorhodomine-B (SRB) assay were evaluated for percent cell viability and IC50 values. Epi-catechin, 4-O-caffeoyl quinic acid, 5-O-caffeoyl quini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
(47 reference statements)
1
0
0
Order By: Relevance
“…This study revealed that the greatest anticancer effects of both of the parts of R. mucronata was on the colon (CaCo-2) and breast (MCF-7) cancer cell lines. This observation agrees with the results reported by Yunos et al [45], who found that Epicatechin, 4-O-caffeoyl quinic acid, 5-Ocaffeoyl quinic acid, and procyanidin B2 isolated from R. mucronata showed strong to moderate anticancer effects on colorectal (HT29) and breast (T47D) cancer cell lines. These results also agree with existing studies on the polyisoprenoids from R. mucronata leaves that induce apoptosis in WiDr colon cancer cells by reducing the expression of Bcl-2 and cyclin D1, consequently causing cell cycle arrest [25].…”
Section: Discussionsupporting
confidence: 93%
“…This study revealed that the greatest anticancer effects of both of the parts of R. mucronata was on the colon (CaCo-2) and breast (MCF-7) cancer cell lines. This observation agrees with the results reported by Yunos et al [45], who found that Epicatechin, 4-O-caffeoyl quinic acid, 5-Ocaffeoyl quinic acid, and procyanidin B2 isolated from R. mucronata showed strong to moderate anticancer effects on colorectal (HT29) and breast (T47D) cancer cell lines. These results also agree with existing studies on the polyisoprenoids from R. mucronata leaves that induce apoptosis in WiDr colon cancer cells by reducing the expression of Bcl-2 and cyclin D1, consequently causing cell cycle arrest [25].…”
Section: Discussionsupporting
confidence: 93%